2016
DOI: 10.11646/zootaxa.4061.2.5
|View full text |Cite
|
Sign up to set email alerts
|

A new record of the freshwater polychaete Namanereis hummelincki <br />(Polychaeta: Nereididae) from epigean waters of Montserrat

Abstract: The presence of the freshwater polychaete, Namanereis hummelincki (Augener), on Montserrat is documented for the first time. Although collected in the sediment of a freshwater stream, this subterranean species most likely lives in groundwater aquifers. A mitochondrial cytochrome c oxidase subunit I (COI) sequence obtained from this material supports assignment to the genus Namanereis Chamberlin, and morphological analysis supports identification as N. hummelincki. Differences in jaw morphology observed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Therefore, the Canary Islands had to be colonized by marine Namanereis ancestors from the African continent, ancient islands of Palaeo-Canaries (Carracedo 2011), or the Mediterranean basin. Shoobs et al (2016) found that the two new Canarian species together were sister to specimens identified as N. hummelincki from Montserrat, Caribbean. This is not surprising considering the general morphological similarity between the Caribbean N. hummelincki and N. canariarum.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Therefore, the Canary Islands had to be colonized by marine Namanereis ancestors from the African continent, ancient islands of Palaeo-Canaries (Carracedo 2011), or the Mediterranean basin. Shoobs et al (2016) found that the two new Canarian species together were sister to specimens identified as N. hummelincki from Montserrat, Caribbean. This is not surprising considering the general morphological similarity between the Caribbean N. hummelincki and N. canariarum.…”
Section: Discussionmentioning
confidence: 84%
“…They cover some 9,000 species worldwide (Glasby 2008). The subfamily Namanereidinae, with the genera Namanereis and Namalycastis, is a monophyletic group with over 40 described species of nereidids adapted to live in low salinity habitats (Glasby et al 2016), with some species that have even colonized semi-terrestrial and subterranean environments (Solís-Weiss and Espinasa 1991;Glasby, 1999;Shoobs et al 2016). The genus Namanereis currently contains about 20 valid species distributed from the tropics to high latitudes (Read and Bellan 2014;Conde-Vela 2017), almost exclusively occurring in intertidal and uplifted coastal areas, often far from the sea.…”
Section: Introductionmentioning
confidence: 99%
“…Over centuries, annelids had been classified into three classes; Polychaeta (marine worms), Oligochaeta (Earthworms) and Hirudinea (Leeches). Among these, polychaeta is the largest group in the phylum, mostly comprised by marine worms and few (about 2%) are fresh water species (Glasby and Timm, 2008;Shoobs et al, 2016). There are about 11,456 species of polychaetes which are distributed in a wide range of habitats; wetlands, sandflats, intertidal zones and deep seas (Kriska, 2013;Pamungkas et al, 2019).…”
Section: Taxonomy and Distribution Of Polychaetesmentioning
confidence: 99%
“…Collected specimens were transferred to 70% ethanol within three weeks and stored in the New York State Museum (NYSM 71909). Genomic DNA from one specimen was extracted to amplify the mitochondrial COI gene following Shoobs et al (2016).…”
Section: U N C O R R E C T E D P R O O F S -N O T F O R D I S T R I Bmentioning
confidence: 99%